Collection Level Description: Strossmayer Gallery of Old Masters Example - Vujić, Žarka (Array, 2003)
Collection Management is now an established and clear term which encompass as umbrella a whole chain of procedures concerning the museum collections. But were the collections really in the centre of our interest or are we talking all the time about the managing and documenting of the museum objects or groups of objects instead of the collectionsé Trying to find answer on this question, idea about the collection description research was born. The challenges came from the two sources, from the theoretical museology as well as from collection description projects. In this article the first one will be represented by the researching of the real museum collection description needs and in the light of that by the analysing of the existed international museum data structure standards like as CIDOC Guidelines, CDWA etc. As the second challenge DCMI Collection Working Group description scheme as the most important one in the documenting of the collections in the virtual environment (collection of museum objects representations, digital libraries, archives etc.) is recognised. Scheme is based on the Dublin Core and Collection Level Description (Research Support Libraries Programme, UKOLN) and it is devided in the four main parts regarding collection, location, persons/institutions and external relationships. Collection description becomes very important in the context of global information environment. Many museums provide public access to their collection management databases over the Internet, but content of those databases is not searchable through Web search engines such as Google or Altavista, because this content is represented by dynamically created web pages. This problem, known as “ deep web” , in cultural heritage community could be partially neutralised by use of collection-level description that can help Web users discover the museums’ resources. The metadata scheme and all its categories and relations will be carefully studied and finally used for description of private collections donated to the City of Zagreb. Few of those collections are already documented in museum information systems and also have their on-line catalogues available on web. It would be interesting to see how is relationship between object-level and collection-level description going to be established. Collections donated to the City of Zagreb are in custody of individual museums, consequently, their information resources are also distributed. It is possible to use collection-level description for distributed resources that can be contributed to centralised services (e.g., a subject gateway, cultural heritage portal, search engine) to be more available to users. Thus, results of this case study can be useful to this year CIDOC conference which pass under the slogan "World Cultural Heritage: Uniting by Understanding".